SIFAT FISIK DAN KIMIA PADA KRUPUK LOBAK (Raphanus Sativus L) DENGAN BERBAGAI TEPUNG KOMPOSIT TERIGU DAN MOCAF - Bekti K., Endang; Fitriana, Ika (Faculty of Agricultural Technology, Universitas Semarang, 2022)
Crackers known as complementary food that is very popular among people unfortunately crackers considered less fiber content because the majority are carbohydrates Empowerment radish with processing into refined products that crackers are higher in fiber and vitamins can increase the diversity of crackers therefore how to modificate crackers formulation with radishmixed with wheat-mocaf flour composite can be obtained crispy crackers and have higher levels of fiber and nutrients better than crackers in general .The study aims to determine the differences in the composite between wheat mocaf flour with radish can affect the crackers produce ,which has differently in crispness , moisture content , fiber content and vitamin C. Research was carried out in March 2014 in the Food Engeneering laboratory Agricultural Technology Department of University Semarang. The experimental design is Completely RandomizedDesign( CRD) with five treatments and repeated 4 times , while the treatment is :